Studies on Reference Intervals for Platelet Counts in Three Cities in China and one in Japan - Ruan, Changgeng; Wu, Yun; Okada, Tokuhiro; Motoi, Shigemi; Kondo, Tamiaki; Jiang, Meiyi; Xin, Xiaomin; Peng, Liming; Ichihara, Kiyoshi; Ikeda, Yasuo (Thrombosis and Haemostasis, 2002)
Hematological parameters including platelet counts, etc. were determined in 1,140 healthy subjects living in four cities: Suzhou (Jiangsu Province), Chengdu (Sichuan Province) and Harbin (Heilongjang Province) in China, and Kobe in Japan. Then, the reference intervals for platelet counts were calculated and compared. The reference interval for platelet count of subjects aged between 18 and 60 years was 60-259 × 109/L in Suzhou and 52–202 × 109/L in Chengdu, and subjects with platelet counts of 100 × 109/L or less accounted for about 30% of the subjects examined in these cities. The reference intervals in Harbin and Kobe were within the range of 150–350 × 109/L, and no subject having a platelets count of 100 × 109/L or less was detected. Mean platelet volume (MPV) determined concurrently was negatively correlated with platelet count, and the reference intervals for MPV in Chengdu and Suzhou were higher than those in Harbin and Kobe.
Keywords: Platelet count; reference interval; MPV; bleeding time; China